Gains from international monetary policy coordination: does it pay to be different? - Zheng Liu; Evi Pappa (European Central Bank (ECB), 2005)
This paper presents a new argument for international monetary policy coordination based on considerations of structural asymmetries across countries. In a two-country world with a traded and a non-traded sector in each country, optimal independent monetary policy cannot replicate the natural-rate allocations. There are potential welfare gains from coordination since the planner under a cooperating regime internalizes a terms-of-trade externality that independent central banks tend to overlook. Yet, with symmetric structures across countries, the gains are quantitatively small. If the size of the traded sector differs across countries, the gains can be sizable and increase with the degree of asymmetry. The planner's optimal policy not only internalizes the terms-of-trade externality, it also creates a terms-of-trade bias in favor the country with a larger traded sector. Further, the planner tries to balance the terms-of-trade bias against the need to stabilize fluctuations in the terms-of-trade gap.
Keywords: E52; F41; F42; 330; Asymmetric Structures; International Policy Coordination; optimal monetary policy; Terms-of-Trade Bias; Internationale Wirtschaftspolitik; Geldpolitik; Wohlfahrtsanalyse; Terms of Trade; Theorie